Anticoagulation Monitoring Under ECMO Support: A Comparative Study Between the Activated Coagulation Time and the Anti-Xa Activity Assay. (July 2020) - Delmas, Clément; Jacquemin, Aemilia; Vardon-Bounes, Fanny; Georges, Bernard; Guerrero, Felipe; Hernandez, Nicolas; Marcheix, Bertrand; Seguin, Thierry; Minville, Vincent; Conil, Jean-Marie; Silva, Stein
Purpose: Extra Corporeal Membrane Oxygenation (ECMO) is used in cases of severe respiratory and/or circulatory failure over periods of several days to several weeks. Its circuitry requires a closely monitored anticoagulation therapy that is empirically supported by activated clotting time (ACT)—a method often associated with large inter- and intraindividual variability. We aimed to compare the measurement of heparin activity with ACT and the direct measurement of the heparin activity (anti-Xa) in a large ECMO population. Methods: All patients treated by venoarterial or venovenous ECMO in our intensive care unit between January 2014 and December 2015 were prospectively included. A concomitant measurement of the anti-Xa activity and ACT was performed on the same sample collected twice a day (morning–evening) for unfractionated heparin adaptation with an ACT target range of 180 to 220 seconds. Results: One hundred and nine patients (men 69.7%, median age 54 years) treated with ECMO (70.6% venoarterial) were included. Spearman analysis found no correlation between anti-Xa and ACT (ρ < 0.4) from day 1 and worsened over time. Kappa analysis showed no agreement between the respective target ranges of ACT and anti-Xa. Conclusions: We demonstrate that concomitant measurement of ACT and anti-Xa activity is irrelevant in ECMO patients. Since ACT is poorly correlated with heparin dosage, anti-Xa activity appears to be a more suitable assay for anticoagulation monitoring.